ISLAM AND THE POLITICAL AND SOCIOECONOMIC DEVELOPMENT MODEL OF THE MUSLIM STATES - YOVKOCHEV, Shukhrat (CENTRAL ASIA AND THE CAUCASUS, 2008)
In the last quarter of the 20th century, the political processes in the Islamic world showed beyond the shadow of a doubt that religion is still a viable part of public life in the Muslim countries. moreover, certain states, such as Iran, Pakistan, Egypt, Afghanistan, Saudi Arabia, and Syria, have restored religion to its rightful place in their policy. The comment by American political scientist John Esposito to the effect that Islamic ideology, symbols, slogans, and actors became prominent fixtures in Muslim politics suits these countries well.1 The stable influence of Islam on sociopolitical life is largely explained by the particular features of Muslim teaching. Islam is usually considered a system that regulates many aspects of people’s lives.n this interpretation, Islam is not only a religious system, but also offers a model for organizing so-ciety. Moreover, some Muslim scientists believe that sociopolitical activity is a religious duty in Is-lam, and that it is a religious obligation for a Muslim to remain aware of the political realities around him.2 The “ideological meaning” of Islam, in the opinion of Shaukat Ali, a representative of Islamic thought, is also increased by the fact that every Muslim is under religious obligation to understand and respect the past.3 The “past” implies the “unique period” of the life of the Prophet Muhammad and the four righteous caliphs.4 In this way, the “ideal past” serves as a model for a perfect human society, to which believers should strive. As Hasan al-Banna (1906-1949),5 an Egyptian ideologist of Islamism, claimed that the conflict characteristic of Europe between spiritual and secular principles, between religion and the state, has no place in Islam …The Christian idea of “give to Caesar what is Caesar’s, and to God what is God’s”is missing here, since everything belongs to Almighty Allah.6 From this point of view, Islam is not only a religion, but also a “way of life,” it contains the solution to social, political, and other secular issues.7 According to Muslim fundamentalists, reform in Islam does not mean modification or changes in the way of thinking and practice established by the Prophet and his companions, rather “purifying Islam” of “alien” elements which supposedly deprive it of its original clarity, simplicity, and power. Such ideologists as Hasan al-Banna and Pakistani fundamentalist Abu al-A’la al-Maududi (1903-1979)8 upheld “theocracy” as an ideal form of statehood. But the representatives of reformative thought in Islam categorically rejected theocracy as a phenomenon incompatible with faith and not espousing the institution of clergy. As Muhammad Abdo (1834-1905)9 emphasized, Islam placed man face to face with God and taught him to manage without any intercession.10 More radical reformers were consistent “secularists.” Ali Abd ar-Razik (1888-1966), who was under the great influence of Muhammad Abdo, “went much further than his ideological mentor, emphasizing the need to separate religion from the state. He referred to the fact that Muhammad was only a prophet and his preaching was not political in nature.”11 According to the provisions of Ali Abd arRazik, the Prophet did not leave an example of an Islamic state.12 Therefore, according to him, Muslims should rid themselves of the belief that they need a caliphate and use their own minds (aql) to look for solutions to social and political problems.